MEDICAL NUTRITION FOR NON SPECIFIC ULCERATIVE COLITIS AND CROHN'S DISEASE IN CHILDREN - O.A. Tutina; E.N. Fedulova; V.N. Kopeikin; O.V. Fedorova; A.R. Bogomolov (Union of pediatricians of Russia, 2008)
Disturbances of nutritive status are typical of patients with non specific ulcerative colitis и crohn's disease with such symptoms as body weight deficiency, disturbance of metabolism associated with the lack of proteins, macro and microelements, energy substrata. Nutrition plays a key role not only in the growth and development processes but also is one of the crucial factors determining the adequacy of the inflammatory response, adaptation compensatory processes. The article considers issues of medicated nutrition under this pathology, including the basic diet, usage of specialized mixes and enteral feeding to correct the protein energy disturbances, and as an independent treatment method.Key words: crohn's disease, non-specific ulcerative colitis, children, diet, enteral feeding, bowel disease.